CURRENT STATE OF DESIGN EDUCATION IN UKRAINE - Аверьянова, Нина; Гук, Леонид (SWorldJournal, 2022)
The article shows that design in the modern world plays a significant role both for the economic competitiveness of the state and for improving the quality of life of people. Modern design demonstrates that it is gradually transforming. It is associated